Histamine 1 receptor-Gβγ-cAMP/PKA-CFTR pathway mediates the histamine-induced resetting of the suprachiasmatic circadian clock. Issue 1 (December 2016) - Kim, Yoon; Kim, Young-Beom; Kim, Woong; Lee, Seung; Oh, Seog; Han, Hee-Chul; Lee, C.; Colwell, Christopher; Kim, Yang
Abstract Background Recent evidence indicates that histamine, acting on histamine 1 receptor (H1R), resets the circadian clock in the mouse suprachiasmatic nucleus (SCN) by increasing intracellular Ca2+ concentration ([Ca2+ ]i ) through the activation of CaV 1.3 L-type Ca2+ channels and Ca2+ -induced Ca2+ release from ryanodine receptor-mediated internal stores. Results In the current study, we explored the underlying mechanisms with various techniques including Ca2+ - and Cl− -imaging and extracellular single-unit recording. Our hypothesis was that histamine causes Cl− efflux through cystic fibrosis transmembrane conductance regulator (CFTR) to elicit membrane depolarization needed for the activation of CaV 1.3 Ca2+ channels in SCN neurons. We found that histamine elicited Cl− efflux and increased [Ca2+ ]i in dissociated mouse SCN cells. Both of these events were suppressed by bumetanide [Na+ -K+ -2Cl− cotransporter isotype 1 (NKCC1) blocker], CFTRinh -172 (CFTR inhibitor), gallein (Gβγ protein inhibitor) and H89 [protein kinase A (PKA) inhibitor]. By itself, H1R activation with 2-pyridylethylamine increased the level of cAMP in the SCN and this regulation was prevented by gallein. Finally, histamine-evoked phase shifts of the circadian neural activity rhythm in the mouse SCN slice were blocked by bumetanide, CFTRinh -172, gallein or H89 and were not observed in NKCC1 or CFTR KO mice. Conclusions Taken together, these results indicate that histamine recruits the H1R-Gβγ -cAMP/PKA pathway in the SCN neurons to activate CaV 1.3 channels through CFTR-mediated Cl− efflux and ultimately to phase-shift the circadian clock. This pathway and NKCC1 may well be potential targets for agents designed to treat problems resulting from the disturbance of the circadian system.